EKSPLORASI ETNOMATEMATIKA DALAM TRADISI PERNIKAHAN ADAT DAYAK KEBAHAN DI KECAMATAN BELIMBING KABUPATEN MELAWI - Agustina Rezha Cantika; Ahmad Yani T; Munaldus Munaldus (STKIP Singkawang, 2022)
There is a relationship between cultural activities and education; this education applies to all subjects, one of which is mathematics. The relationship between mathematics and culture is called ethnomathematics. One of the cultural activities that has a relationship with mathematics is the traditional wedding tradition. Traditional wedding traditions are often carried out every year, and many people are interested in attending and witnessing the traditional wedding tradition taking place. Unbeknownst to the public, they have witnessed some mathematical activity. Many people still think that mathematics is something foreign and difficult, even though they just don't realize that so far every activity they have done has mathematics in it. In order to raise awareness of the role of mathematics in everyday life, a study of ethnomathematical activities and mathematical ideas embedded in the Dayak Kebahan traditional wedding ritual has been conducted. This study employed an ethnographic approach and a qualitative research methodology. by observing and interviewing two people as research subjects to get research results that are in accordance with the existing problem formulation. The results of the research show that there are ethnomathematical activities and mathematical concepts in the traditional Dayak Kebahan wedding tradition.